perilaku hidup bersih dan sehat sebagai faktor resiko yang berhubungan dengan kejadian diare akut pada balita di wilayah puskesmas aikmel - , ROBIATUL ADAWIYAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In some developing countries diarrhea is also one of the main causes of morbidity and mortality in children under five years old is also included in Indonesia. Based on Health Research Association in 2013 that the incidence of diarrhea in West Nusa Tenggara Province still above the national average (3.5 percent) namely 4.1 percent. It can be caused by several factors including maternal factors, child factors, environmental factors and socioeconomic factors. Objectives: This study was conducted to determine health and clean life style as risk factor behavior associated with incidence of diarrhea children under five years in Aikmel primary health center, East Lombok District in West Nusa Tenggara Province. Method: This study used case-control design with a total sample of 84 people to a group of cases and a group of 84 control group. The instrument used to obtain the data is by using questionnaires. The data analysis was performed using univariate, bivariate and multivariate. Result: the variables associated with the incidence of acute diarrhea in children under five years is exclusive breastfeeding (OR=5,77, 95% CI 1,22-27,31), hand washing before giving/feeding a child (OR=2,36, 95% CI 1,35-4,12), hand washing after touching animals (OR=2,41, 95% CI 1,15-5,07) and child excreta disposal site (OR=0,197, 95% CI 0,04-0,94). Conclusion: exclusive breastfeeding, hand washing before giving/feeding a child, hand washing after touching animals and child excreta disposal site a risk factor for acute diarrhea in children under five years.